Wind Speed Regression Model in Forecasting Wave Height in the Shipping Channel Zone - Asmaul Husnah; Abdillah, Abdillah; Vera Mandailina; Syaharudin, Syaharudin; Mehmood, Saba (Universitas Pendidikan Ganesha, 2023)
Nowadays, there are often accidents such as the sinking of ships in water areas that are caused by weather factors, one of which is the extreme wind speed. Wind speed and strong waves in the sea are interrelated because the factor that affects the strength of the wave blow is wind speed. This study aims to provide information about the angina speed regression model to find out the wave height at the sea crossing port. This research is a quantitative research. The data used is in the form of wind speed data taken at the coordinates of Lembar Port and Labuan Bajo Port from the NASA sub-agroclimatology website from January 1, 2012, to December 31, 2021 (for 10 years). This case study uses linear regression analysis and is operated using SPSS software. The data shows that in Lembar Port has the most extreme wind speed fluctuations in the 6th and 7th years. While the wind speed fluctuations in Labuan Bajo are consistent, but slightly extreme in the 7th year surpassing the 1st year. The results showed that the R-Square of Lembar port was 15.4% while the R-Square of Labuan Bajo port was 16.2%. The results of this study can be used in formulating marine transportation safety policies in both regions.